Metropolis algorithms, logit and quantile regression estimation - Allenby, Greg M. (Henry Stewart Talks, 2010)
Review of Markov chains, Stationary distribution, Time reversible chains, Metropolis methods, Discrete case: Metropolis-Hastings algorithm, Independence chains, Random walk chains, Relative numerical efficiency, The Gibbs sampler, Logit model, Scaling rw metropolis, Quantile regression, Asymmetric Laplace distribution